2022
DOI: 10.1101/2022.03.29.486265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inositol hexakisphosphate (IP6) accelerates immature HIV-1 Gag protein assembly towards kinetically-trapped morphologies

Abstract: During the late stages of the HIV-1 lifecycle, immature virions are produced by the concerted activity of Gag polyproteins, primarily mediated by the capsid (CA) and spacer peptide 1 (SP1) domains, which assemble into a spherical lattice, package viral genomic RNA, and deform the plasma membrane. Recently, inositol, hexakisphosphate (IP6) has been identified as an essential assembly cofactor that efficiently produces both immature virions in vivo and immature virus like particles in vitro. To date, however, se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…None of the Myr groups at the trimer-trimer interface exhibit Myr insertion although they are in 'Myr-exposed' states. On the other hand, in the random dimer model (Figure 2), 4 Myr groups are at a stable inserted state at the end of the 5 µs trajectory. In both simulations, at least one Myr group remained in the sequestered state.…”
Section: Membrane Binding and Myr Insertion Of Matrix (Ma) Trimer Ass...mentioning
confidence: 97%
See 1 more Smart Citation
“…None of the Myr groups at the trimer-trimer interface exhibit Myr insertion although they are in 'Myr-exposed' states. On the other hand, in the random dimer model (Figure 2), 4 Myr groups are at a stable inserted state at the end of the 5 µs trajectory. In both simulations, at least one Myr group remained in the sequestered state.…”
Section: Membrane Binding and Myr Insertion Of Matrix (Ma) Trimer Ass...mentioning
confidence: 97%
“…The Gag polyprotein consists of the matrix (MA), Capsid (CA), spacer-peptide 1 (SP1), nucleocapsid (NC), spacer-peptide 2 (SP2), and p6 domains. While the CA and NC domains contribute to Gag multimerization and RNA encapsidation during the viral assembly [3][4][5] , the p6 domain plays an important role in viral budding. Membrane targeting to the PM and recruitment of the Envelope(Env) protein is mediated by the MA domain, which is post-translationally acylated with a myristate (Myr) group in its N-terminus [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…IP6 interacts with the six-helix bundle structure and stabilizes the immature Gag lattice. IP6 is also very crucial for assembly of CA into the mature fullerene-like cone lattice [187][188][189][190][191][192].…”
Section: Maturation Inhibitorsmentioning
confidence: 99%
“…The polyanion, IP6, binds the rings of basic LYS residues (LYS290, LYS359) and the mutations of either LYS residues have been observed to disrupt immature viral particle production and infectivity (37,38). A recent coarse-grained molecular dynamics (CGMD) study revealed that other than the role of IP6 as an assembly accelerator, it promotes kinetically-trapped fissure-like defects in the immature lattice which might play an important role in the later stages of the viral replication cycle (39). In addition, homo-dimeric and homo-trimeric interactions are mediated by the CANTD and CACTD residues.…”
Section: Introductionmentioning
confidence: 99%